2020
DOI: 10.35772/ghm.2020.01089
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte ploidy and pathological mutations in hepatocellular carcinoma: impact on oncogenesis and therapeutics

Abstract: Hepatocellular carcinoma (HCC) occurs in the chronic liver inflammation such as viral hepatitis, alcoholic and non-alcoholic steatohepatitis. While anti-viral treatment has been significantly improved, the prevalence of HCC remains high and treatment is still challenging. The continuation of hepatocyte death, inflammation, and fibrosis leads to the accumulation of gene alterations, which may trigger carcinogenesis. Hepatocytes are a unique cell type having more than one complete set of 23 chromosomes, termed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Chronic liver disease with fibroinflammation contributes not only to fibrosis but also hepatocyte regeneration as well as replication-induced DNA damage, all of which may promote the development of liver cancer. [134][135][136][137][138][139] Extensive data have described exosomes as carriers of various cargoes conveying cellular information that enables them to serve as important players in malignant cell-nonmalignant cell communication during cancer developemnt. 88,[140][141][142] miRNA expression profiling of HSCs cocultured with liver cancer cells showed that miR-148a-3p was significantly reduced in HSCs.…”
Section: Liver Cancermentioning
confidence: 99%
“…Chronic liver disease with fibroinflammation contributes not only to fibrosis but also hepatocyte regeneration as well as replication-induced DNA damage, all of which may promote the development of liver cancer. [134][135][136][137][138][139] Extensive data have described exosomes as carriers of various cargoes conveying cellular information that enables them to serve as important players in malignant cell-nonmalignant cell communication during cancer developemnt. 88,[140][141][142] miRNA expression profiling of HSCs cocultured with liver cancer cells showed that miR-148a-3p was significantly reduced in HSCs.…”
Section: Liver Cancermentioning
confidence: 99%
“…ANXA6, S100A10, AURKA, AURKB, LGALS1), [64][65][66][67] cell proliferation and exertion of biomechanical forces (i.e. MKI67, KRT19, VIM, CDC25C), [68][69][70][71] as well as nuclei reorganization (i.e. H2AC8, H4C6, H2BC9, H2BC13, H3C7, H2AC16), [72,73] suggesting that the 3D polymer-based scaffolds may restrict -but not hinder-their proliferation, facilitating the cell-cell fusion and/or interfering with the cellular cytokinesis, enabling the generation of PGCC.…”
Section: Resultsmentioning
confidence: 99%
“…Both single-and double-stranded breaks (SSB and DSB) are a common feature of cell karyotype studies after cannabis exposure [7][8][9][10]12,13,99]. It therefore becomes important in the present context to note that the epigenome plays an often determinative role in influencing or selecting the site of DNA breakage generally [118][119][120][121][122][123][124][125][126][127][128][129][130][131], during meiotic crossing over [132][133][134][135][136][137][138][139], in the immune gene hypervariable region [140][141][142][143][144][145][146], and in oncogenic pathways [120,123,124,[147][148][149][150][151][152][153]…”
Section: Epigenomic Impacts On Dna Breakage Sitesmentioning
confidence: 99%
“…This tumor almost invariably involves the development of an isochromosome 12p. Its presence is explained by the concept of presumptive pericentromeric chromatin dysregulation as the dysregulated pericentromeric epigenome presumably facilitates the aberrant scission of the chromosome at the centromere, forming the isochromosome through the interactions between the epigenome and the genome as described above [118][119][120][121][122][123][124][125][126][127][128][129][130][131]. The presence of KIT and KRAS (and to a lesser extent NRAS) on chromosome 12 then confers a growth advantage on the mutant clone, and malignant tumorigenesis is the end result of this process continued in the context of the gross re-sculpting of the chromosomal landscape by repeated cycles of the breakage-fusion-bridge cycle across multiple cell divisions that accumulate over time.…”
Section: Cannabinoids Deliver Multiple Carcinogenic Insultsmentioning
confidence: 99%